Stochastic Homogenization of Monotone Systems of Viscous Hamilton--Jacobi Equations with Convex Nonlinearities - Fehrman, B (Society for Industrial and Applied Mathematics, 2013)
We consider the homogenization of monotone systems of viscous Hamilton--Jacobi equations with convex nonlinearities set in the stationary, ergodic setting. The primary focus of this paper is on collapsing systems which, as the microscopic scale tends to zero, average to a deterministic scalar Hamilton--Jacobi equation. However, our methods also apply to systems which do not collapse and, as the microscopic scale tends to zero, average to a deterministic system of Hamilton--Jacobi equations.